2021
DOI: 10.1101/2021.06.17.21258639
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molnupiravir, an Oral Antiviral Treatment for COVID-19

Abstract: Background: Easily distributed oral antivirals are urgently needed to treat coronavirus disease-2019 (COVID-19), prevent progression to severe illness, and block transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We report the results of a Phase 2a trial evaluating the safety, tolerability, and antiviral efficacy of molnupiravir in the treatment of COVID-19 (ClinicalTrials.gov NCT04405570). Methods: Eligible participants included outpatients with confirmed SARS-CoV-2 infection and s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
181
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(192 citation statements)
references
References 23 publications
3
181
0
8
Order By: Relevance
“…Animal testing trials have also found it to be effective in reducing viral load (18,19). Results from a Phase IIa trial indicated a shorter time to viral RNA clearance and a greater proportion of participants achieving overall clearance with 800 mg of molnupiravir compared to a placebo (20). Molnupilavir was generally well tolerated, with a similar number of adverse events in all groups.…”
Section: Advance Publicationmentioning
confidence: 98%
“…Animal testing trials have also found it to be effective in reducing viral load (18,19). Results from a Phase IIa trial indicated a shorter time to viral RNA clearance and a greater proportion of participants achieving overall clearance with 800 mg of molnupiravir compared to a placebo (20). Molnupilavir was generally well tolerated, with a similar number of adverse events in all groups.…”
Section: Advance Publicationmentioning
confidence: 98%
“…Hence, some other possible RdRp inhibitors are being considered for COVID-19 treatment, which includes molnupiravir, galidesivir, ribavirin, sofosbuvir, and tenofovir [14,15]. Recently molnupiravir, an orally active RdRp inhibitor with a favorable pharmacokinetic profile, has received considerable attention owing to its ability to inhibit SARs-COV-2 replication, its quick clearance of SARs-COV-2, and the accompanying reduction in viral load and fast recovery time [20]. Molnupiravir reaches quantifiable concentration in 0.5 h between 600-1600 mg. Administration of a single dose produces mean C max values up to 13.2 ng/mL and shows median t max between 0.25 and 0.75 h and a biological half-life (t 1/2 ) of 7 h. Its C max and area under the plasma concentration versus time curve (AUC) increases in a dose-proportional manner with no accumulation following multiple doses suggesting that molnupiravir has no accumulative toxicity.…”
Section: Rna-dependent Rna-polymerase (Rdrp)mentioning
confidence: 99%
“…Remdesivir (moderately ill patients [10,11], per the metaanalysis of the two trials) Monoclonal antibodies [18][19][20] Molnupiravir [15,16] 25-75% reduction in chance of hospitalisation…”
Section: Role Of the Funding Sourcementioning
confidence: 99%
“…Postulated for Monoclonal antibodies due to effect on viral loads [18][19][20] Possibly Molnupiravir [15,16] Possibly Peginterferon-Lambda [17] 25-75% reduction in duration of infectiousness 25-50%…”
Section: Reduce Duration Of Infectiousnessmentioning
confidence: 99%